Economics and Ageing Volume IV: Political Economy - Iparraguirre, José Luis.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This upper level textbook provides a coherent introduction to the economic implications of individual and population ageing. Placing economic considerations into a wider social sciences context, this is ideal reading not only for advanced undergraduate and masters students in health economics and economics of ageing, but policy makers, professionals and practitioners in gerontology, sociology, health-related sciences, and social care. This volume introduces topics in the economics of happiness, quality of life, and well-being in later life. It also covers questions of inequality and poverty, intergenerational economics, and housing. Other areas described in this book include behavioural economics, political economy, and consumption in ageing societies.
1. Conceptualisations and Measurement -- 2. Theories and Empirical Findings -- 3. Happiness and Policy -- 4. Inequality -- 5. Poverty, Deprivation and Social Class -- 6. Some Questions of Intergenerational Economics -- 7. Ageing, House Prices, and Economic Crises -- 8. Behavioural Economics and Individual Ageing -- 9. Behavioural Economics and Policy -- 10. Economics and the Political Economy of Ageing -- 11. Gerontological Views -- 12. The Silver Economy.
Keywords: elektronické knihy; electronic books; Medical economics; Aging; Evolutionary economics; Institutional economics; Finance, Public; Population -- Economic aspects; Labor economics; Health Economics; Ageing; Institutional and Evolutionary Economics; Public Economics; Population Economics; Labor Economics